Construction Owner's Role In Construction Safety (Private Sector) - Khor, Boon Sian (2007)
The construction industry has long been regarded as one of the most dangerous industries and still problematic areas that need to be addressed by all parties concerned. Perindustrian pembinaan, salah satu daripada industri-industri yang lain maih mempunyai pelbagai masalah yang berbahaya patut dibincangkan oleh badan-badan tertentu.